2013
DOI: 10.1111/ceo.12143
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between decreased choroidal blood flow velocity and the pathogenesis of acute zonal occult outer retinopathy

Abstract: In eyes with acute zonal occult outer retinopathy, the mean blur rate at the affected area significantly increases along with improvement of visual functions. These results suggest that impaired choroidal circulation is involved in the pathogenesis of acute zonal occult outer retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
(39 reference statements)
1
35
0
Order By: Relevance
“…S1A; right, dotted line). To evaluate changes in average MBR, the changing rate of average MBR against the initial baseline value was used, as previously described, 17,[19][20][21][22][23][24][25][26] since the MBR is an index of ''relative'' blood flow velocity. …”
Section: Mean Blur Rate Measurements On Lsfgmentioning
confidence: 99%
“…S1A; right, dotted line). To evaluate changes in average MBR, the changing rate of average MBR against the initial baseline value was used, as previously described, 17,[19][20][21][22][23][24][25][26] since the MBR is an index of ''relative'' blood flow velocity. …”
Section: Mean Blur Rate Measurements On Lsfgmentioning
confidence: 99%
“…5 Although LSFG does not provide an absolute value for the blood flow, this technique has the advantage of allowing precise and repeated measurements of choroidal circulation at various intervals during the time course of diseases. 4 We have recently revealed that the MBR decreased in the acute stage of the choroidal inflammatory diseases, including Vogt-Koyanagi-Harada disease 6 and acute zonal occult outer retinopathy, 7 whereas it increased in acute central serous chorioretinopathy 8 due to a noninflammatory (i.e. sympathetic or adrenergic) etiology.…”
mentioning
confidence: 99%
“…Each average MBR was automatically calculated for each square using the software. To evaluate changes in average MBR, the changing rates of average MBR against the initial baseline values (defined as 100 %) were used, as previously described [11][12][13], since MBR is a quantitative index of the "relative" blood flow velocity.…”
Section: Ophthalmologic Examinationsmentioning
confidence: 99%
“…Recently, laser speckle flowgraphy (LSFG) has been used to investigate ocular blood flow velocity [7][8][9][10][11][12][13]. The wavelength of 830 nm for a diode laser used in LSFG can penetrate deep into the choroid, as demonstrated in composite color map images depicting the large choroidal vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation